MEKK1-MKK4-JNK-AP1 Pathway Negatively Regulates Rgs4 Expression in Colonic Smooth Muscle Cells - Zhang, Yonggang; Li, Fang; Liu, Shu; Wang, Hong; Mahavadi, Sunila; Murthy, Karnam S.; Khalili, Kamel; Hu, Wenhui (PLOS ONE, 2012)
Background Regulator of G-protein Signaling 4 (RGS4) plays an important role in regulating smooth muscle contraction, cardiac development, neural plasticity and psychiatric disorder. However, the underlying regulatory mechanisms remain elusive. Our recent studies have shown that upregulation of Rgs4 by interleukin (IL)-1β is mediated by the activation of NFκB signaling and modulated by extracellular signal-regulated kinases, p38 mitogen-activated protein kinase, and phosphoinositide-3 kinase. Here we investigate the effect of the c-Jun N-terminal kinase (JNK) pathway on Rgs4 expression in rabbit colonic smooth muscle cells. Methodology/Principal Findings Cultured cells at first passage were treated with or without IL-1β (10 ng/ml) in the presence or absence of the selective JNK inhibitor (SP600125) or JNK small hairpin RNA (shRNA). The expression levels of Rgs4 mRNA and protein were determined by real-time RT-PCR and Western blot respectively. SP600125 or JNK shRNA increased Rgs4 expression in the absence or presence of IL-1β stimulation. Overexpression of MEKK1, the key upstream kinase of JNK, inhibited Rgs4 expression, which was reversed by co-expression of JNK shRNA or dominant-negative mutants for MKK4 or JNK. Both constitutive and inducible upregulation of Rgs4 expression by SP600125 was significantly inhibited by pretreatment with the transcription inhibitor, actinomycin D. Dual reporter assay showed that pretreatment with SP600125 sensitized the promoter activity of Rgs4 in response to IL-1β. Mutation of the AP1-binding site within Rgs4 promoter increased the promoter activity. Western blot analysis confirmed that IL-1β treatment increased the phosphorylation of JNK, ATF-2 and c-Jun. Gel shift and chromatin immunoprecipitation assays validated that IL-1β increased the in vitro and ex vivo binding activities of AP1 within rabbit Rgs4 promoter. Conclusion/Significance Activation of MEKK1-MKK4-JNK-AP1 signal pathway plays a tonic inhibitory role in regulating Rgs4 transcription in rabbit colonic smooth muscle cells. This negative regulation may aid in maintaining the transient level of RGS4 expression.